BPKIHS TB Module: An innovative way to teach tuberculosis to medical undergraduates (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Tuberculosis is a major public health problem in Nepal. Medical schools need to practice evidence-based medicine for national TB control programmes. The objective of the study is to know the feedback about TB module from medical undergraduates. Methodology: This is descriptive study designed to know the feedback regarding content and usefulness of TB teaching module from medical undergraduates of BP Koirala Institute of Health Sciences. The total duration of the study was from March 2004 to May 2008. Results: The feedback about the TB teaching module was taken from 471 students. Out of them 64.7% (305) were males and 35.3% (166) females. Almost all students replied that objective of the module was clear and relevant. “TB teaching module is very useful” was the overall comments of the respondents particularly in respect of structured interactive session (SIS), Lecture, and Field visit to Primary Health Care Center, Britain Nepal Medical Trust, Nepal Anti Tuberculosis Association (NATA). Regarding the relevancy of the module, around 98% students’ response was “relevant” and regarding the contents, 11% students’ response was ”content is too much”. Conclusion: It is recommended that this innovative BPKIHS TB module may be implemented in other medical schools of SAARC countries after necessary modifi cations in their own context. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 8-12 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6959